LENGTH OF TEETH ACCORDING TO THE DATA COMPUTED TOMOGRAPHY IN BOYS AND GIRLS DIFFERENT CRANIOTYPES WITH ORTHOGNATHIC BITE - Марченко, А.В. (World of Medicine and Biology, 2016)
Aim of our work – establish features length of teeth, according to the CT scan in boys and girls of different craniotype with orthognathic bite. Materials and methods The primary indicator of the size of teeth and head boys and girls from Podillia with orthognathic bite (defined by 11-points of M.G. Bushan et al.) obtained from the data bank Scientific and Research Center Vinnitsa National Medical University named after Pirogov. For this study used dental cone beam CT scan - Veraviewepocs 3D, Sea (Japan). Research carried out by own-developed scheme within the given characteristics. Volume three-dimensional image - cylinder 8x8 cm - thickness of layer 0.2 / 0,125 mm 0,11-0,48 mSv dose of radiation, voltage and amperage 60-90kV / 2-10mA. The upper and lower incisors, canines, small and first large molar tooth measured their length - the distance from the middle of the cutting edge to the apex of the root. Cephalometric size measurement was conducted within the program of measurements corresponding list of Martin. Craniotype determined by the formula: the largest width of the head x 100 / longest length of head. Established the following distribution of craniotype: mesocephals boys - 16, boys brachycephales - 19, girls mesocephals - 16 girls brachycephales - 26. Statistical analysis of the results was performed using the statistical software package licensed "Statistica 6,0" using non-parametric estimation methods. Results. Discussions It was established that only the value of length of lateral incisor on the upper jaw in boys brachycephales significantly (p